Study on the utilization of electrocoagulation concept as a disinfectant substitute in hospital wastewater - Fikri, Elanda; Djuhriah, Nanny; Hanurawaty, Neneng Y. (Scientific Review Engineering and Environmental Sciences (SREES), 2021)
The purpose of this study is to identify differences in variations of contact time and number of electrode plates in electrocoagulation process on the decrease of total Coliforms in Bandung City hospital wastewater. An experimental research with factorial randomized design. The volume of wastewater sample to check the total Coliforms was a minimum of 100 ml, using 3 treatments and 6 repetitions. Data analysis used was two-way ANOVA test. The results showed that there was no significant difference between the number of plates (p = 0.269), contact time (p = 0.537), and the number of plates and contact time (p = 0.863) with the total Coliforms in electrocoagulation process. The use of 6 plates and 90 min contact time showed the best results in reducing total Coliforms, with effectiveness reaching 88.38%. This means that the concept is quite effective to use as a substitute for disinfectant.